A Review on Soil Nitrogen Sensing Technologies: Challenges, Progress and Perspectives - Liu, Jun; Cai, Haotian; Chen, Shan; Pi, Jie; Zhao, Liye (Agriculture (Basel), 2023)
Nitrogen is a vital ingredient for plant development and growth. It is one of the most crucial indicators of soil fertility and crop growth conditions. For the monitoring of nitrogen loss patterns and the development of crop nitrogen fertilizer application strategies, an accurate determination of soil nitrogen concentration can be a valuable source of information. For the advancement of precision agriculture and the preservation of the natural ecological environment, an accurate, quick, and low-cost determination of soil nitrogen content and its variations is essential. This paper systematically analyzes and summarizes soil nitrogen detection methods by compiling and analyzing the relevant literature, comparing the advantages and disadvantages of various methods, and concluding with a discussion of the most significant challenges and future research trends in this field. This study provides a helpful resource for understanding the current status, application constraints, and future developments of nitrogen-sensing technologies in precision agriculture.